Studi Analisis Daya Dukung Tanah Lempung Berplastisitas Tinggi yang Dicampur Zeolit - Alfian, Rian; Afriani, Lusmeilia; Iswan, Iswan (Universitas Lampung, 2015)
C lay has properties that are not profitable for construction. This is because the bearing capacityof the soil or low CBR have low value. Therefore we need a stabilizing agent that can reduce soilproperties which are unprofitable, usually accompanied by binding to each soil grain with theother .The research was done by testing on clay samples without a mixture and the clay that is mixedwith zeolite with a variation of 6%, 8%, 10%, 12% and 14%. Tests were performed using standardand modified compaction which previously done curing for 14 days. After compaction test, thesamples were soaked for 4 days and then followed by mechanical testing which is CBR test thataimed to determine the bearing capacity value of the soil after the sample was mixed by zeolites.Based on the results of laboratory research, the highest value obtained on the sample CBR claywith a mixture of 14% zeolite with the use of modified compaction with 14 days of curingand 4days of soaking in the amount of 2.78%. This is because the effect of zeolite which can bind clayparticles. So, the more a mixture of zeolite then bearing capacity of the soil also increasing.However, the value of CBR in this research can not be used as subgrade in road constructionbecause of its CBR value ≤ 6%.Keywords: CBR, Soil Clay, Zeolite